Derivation of Epithelial‐Only Airway Organoids from Human Pluripotent Stem Cells. (4th May 2018) - McCauley, Katherine B.; Hawkins, Finn; Kotton, Darrell N.
Abstract: New protocols to efficiently generate functional airway epithelial organoids from human pluripotent stem cells (PSCs) would represent a major advance towards effective disease modeling, drug screening and cell based therapies for lung disorders. This unit describes an approach using stage‐specific signaling pathway manipulation to differentiate cells to proximal airway epithelium via key developmental intermediates. Cells are directed via definitive endoderm (DE) to anterior foregut, and then specified to NKX2‐1+ lung epithelial progenitors. These lung progenitors are purified using cell surface marker sorting and replated in defined culture conditions to form three‐dimensional, epithelial‐only airway organoids. This directed differentiation approach using serum‐free, defined media also includes protocols for evaluation of DE induction, intracellular FACS analysis of NKX2‐1 specification efficiency and enrichment, and approaches for characterization and expansion of airway organoids. Taken together, this represents an efficient and reproducible approach to generate expandable airway organoids from human PSCs for use in numerous downstream applications. © 2018 by John Wiley & Sons, Inc.